10Gbps NRZ-DPSK repeaterless transmission system for terrestrial applications - Khairi, Kharina; Lambak, Zainuddin; Farhan, Mohd Aliff; Abdan, Mohd Ismail; Hamzah, Zulkifli; Fong, Kok Hann (IEEE, 2014)
We investigated the performance of 10Gbps NRZ-DPSK repeaterless transmission system over 300km. The system is demonstrated experimentally over standard Single-Mode Fiber (SMF). The results showed the capability of terrestrial repeaterless transmission systems as a cost effective solution for improving broadband penetration particularly for rural areas.